Communicating a Positive Result at Newborn Screening and Parental Distress - Elisa Lastrucci; Marta Daniotti; Elena Procopio; Giusi Scaturro; Flavia Tubili; Rosanna Martin; Giancarlo la Marca (MDPI AG, 2023)
The assumption of this study is strictly connected to the need to focus and to know more about the impact on the psychological state of the parents whose newborn babies get a positive result at Expanded Newborn Screening (ENS). As clinical experience shows us, this aspect seems to have a potentially lasting resonance on the way the disease will be managed and handled in the family, leading to potential negative effects and repercussions on the child's wellbeing and on the quality of life within the family. On the basis of this and on the evidence emerging from a review of the literature, this study aims to investigate and objectify possible distress indicators elicited at the moment of the communication of a positive result at ENS. Questionnaires containing the Beck Depression Inventory-II, the State-Trait Anxiety Inventory-Y, and the Short Form 36 Health Survey tests were administered to the parents of 87 newborns who received positive results at ENS. The parents of 32 babies expressed the presence of discomfort potentially related to the communication of a positive result at ENS.